A study on Pursuit of Artificial Intelligence in Human Resource Management: A Narrative view - Ganagi Mahesh C.; Rotti Arun A. (ITM Web of Conferences)
This study harnesses the power of narrative to explore how artificial intelligence (AI) transforms Human Resource Management (HRM). The findings illustrate the broad changes that are taking place in key HR activities like recruitment, performance management processes, employee engagement and learning & development as organizations adopt more AI powered tools to enable workforce outcomes. Synthesising current insights and case studies, the paper identifies AI use-cases that help improve processes while supporting data-driven decision-making. But it tackles moral questions too — biases in algorithms, privacy issues around handling data and the iffy territory of how workers might take to using A.I. The methodology makes use of a secondary data analysis, employing thematic analysis to investigate the consequences that AI can mean for HRM. The results bring home the vast possibilities and difficulties associated with utilizing AI, underscoring why HR workers must quickly come to grips with rapid change in tech. Conclusion This study facilitates important contributions to the current debate on AI and future work, providing a comprehensive narrative perspective on what it means for HR professionals and organizations.